Temporal variation in winter flounder recruitment at the southern margin of their range: is the decline due to increasing temperatures? - Able, K. W.; Grothues, T. M.; Morson, J. M.; Coleman, K. E. (ICES Journal of Marine Science, 2014)
Abstract The southern-most stock of winter flounder (Pseudopleuronectes americanus), a cold temperate species of the Northwest Atlantic, has not recovered from overfishing despite continued restrictive measures, and appears to be contracting northward. We regressed larval and settled juvenile abundance (after accounting for adult and larval contribution to variation, respectively) on temperature over several decades from collections in New Jersey, the United States, at the southern edge of their range to determine if increasing temperatures during the first year of life were responsible for this contraction. A significant stock–recruitment relationship at both stages was moderate, explaining 27.5% of the variance for larvae on adults and 20.6% for juveniles on larvae. There was no significant effect of average monthly temperature in explaining variance of the residuals for larvae, or of degree day on explaining the abundance of residuals for juveniles over a months-long settlement period. However, in both cases, residuals were widely distributed at cold temperatures, while they were always low at warm temperatures. Thus, years in which spring temperatures were warm (5–7oC for February, 7–9 for March, and 11–20 for May) always experienced poor recruitment. This threshold effect may result from an intersection with predators in response to temperature, and this may play a more important role than heat stress in determining recruitment success.